RNA interference against viruses: strike and counterstrike - Haasnoot, Joost (Nat Biotechnol, 2007)
RNA interference (RNAi) is a conserved sequence-specific, gene-silencing mechanism that is induced by double-stranded RNA. RNAi holds great promise as a novel nucleic acid–based therapeutic against a wide variety of diseases, including cancer, infectious diseases and genetic disorders. Antiviral RNAi strategies have received much attention and several compounds are currently being tested in clinical trials. Although induced RNAi is able to trigger profound and specific inhibition of virus replication, it is becoming clear that RNAi therapeutics are not as straightforward as we had initially hoped. Difficulties concerning toxicity and delivery to the right cells that earlier hampered the development of antisense-based therapeutics may also apply to RNAi. In addition, there are indications that viruses have evolved ways to escape from RNAi. Proper consideration of all of these issues will be necessary in the design of RNAi-based therapeutics for successful clinical intervention of human pathogenic viruses.